2020
DOI: 10.3390/nu12020515
|View full text |Cite
|
Sign up to set email alerts
|

Natural Magnesium-Enriched Deep-Sea Water Improves Insulin Resistance and the Lipid Profile of Prediabetic Adults: A Randomized, Double-Blinded Crossover Trial

Abstract: Previous in vitro and in vivo studies have shown that the antidiabetic effect of balanced deep-sea water (BDSW) works through the suppression of hyperglycemia and improvement of glucose tolerance. Based on these promising results, we conducted an eight week randomized, double-blinded crossover trial of the effects of BDSW in prediabetic adults. The subjects consumed 440 mL of BDSW (hardness 4000) per day, and maintained an otherwise normal lifestyle and diet throughout. Efficacy assessments were made by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
6
14
0
Order By: Relevance
“…The current study found no effect of magnesium on blood pressure. A lack of effect on blood pressure is in agreement with the findings of some RCTs 20 , 23 , 31 . Prediabetic adults receiving 350 mg of magnesium per day for 8 weeks did not have a change in blood pressure 20 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study found no effect of magnesium on blood pressure. A lack of effect on blood pressure is in agreement with the findings of some RCTs 20 , 23 , 31 . Prediabetic adults receiving 350 mg of magnesium per day for 8 weeks did not have a change in blood pressure 20 .…”
Section: Discussionsupporting
confidence: 90%
“…A lack of effect on blood pressure is in agreement with the findings of some RCTs 20 , 23 , 31 . Prediabetic adults receiving 350 mg of magnesium per day for 8 weeks did not have a change in blood pressure 20 . Another study reported that long-term magnesium supplementation (350 mg daily for 24 weeks) did not change office and 24-h ambulatory blood pressure levels in overweight and obese adults 31 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Ham and Shon (2020) conducted an RCT in which they evaluated the 8-week administration of deep-sea water enriched with Mg versus placebo in 74 individuals with prediabetes. Following the intervention, the authors recorded a significant reduction in LDL-C ( p = 0.003) and TC ( p = 0.006), but HDL-C and TG remained unchanged [ 87 ]. However, in their RCT, Cosaro et al (2014) detected no benefits of Mg supplementation in terms of TC, LDL-C, or TG reduction and HDL-C elevation in a small study group of 7 males aged 23–33 years who had a positive family history for T2DM/MetS versus 7 healthy controls [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the vast majority of the analyzed RCTs reported no variations in HDL-C (n = 19), LDL-C (n = 16), TG (n = 17), TC (n = 14), TC/HDL-C (n = 4), VLDL (n = 2), or LDL-C/HDL-C (n = 1). However, some RCTs reported elevations of the HDL-C (n = 8), apoA1 (n = 1), or HDL-C/TG (n = 1), as well as reductions in LDL-C (n = 7), TC (n = 4), TG (n = 7), TC/HDL-C (n = 2), or VLDL (n = 3) in the participants exposed to the Mg intervention [ 13 , 14 , 18 , 35 , 36 , 38 , 41 , 42 , 43 , 53 , 80 , 82 , 83 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 95 , 96 , 98 , 99 , 105 , 109 , 111 , 113 , 123 ].…”
Section: Discussionmentioning
confidence: 99%